Prevalence and Infection Rate of Three Gizzard Nematodes in the Mallard Anas Platyrhynchos L., 1758 Collected in Al-Diwaniya and Diyala Provinces , Central Iraq - Mohammad, M. K.; Al-Moussawi, A. A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2016)
Three nematodes : Amidostomum  acutum , Epomidiostomum uncinatum and Hadjelia truncata , were recovered from the gizzards of wintering mallard collected at two sites in central Iraq. A brief description of the parasites along with some notes on their infection rate, prevalence and discussion with the pertinent literature are provided.